GENETIC ASPECTS OF TOOTH AND PERIODONTAL TISSUE DEVELOPMENT - Pomanyuk, A.M.; Кузенко, Є.В. (World of Medicine and Biology, 2012)
This article is hovering the genes and polypeptides that play a metabolic processes during the synthesis and maturation of follicles forming teeth and alveolar bone. Examples of genetic diseases induced by irregularities in the activity of the gene, which encodes several polypeptides.